2022
DOI: 10.1371/journal.pone.0265733
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of symptomatic dry eye disease with associated risk factors among medical students at Chiang Mai University due to increased screen time and stress during COVID-19 pandemic

Abstract: Dry eye disease (DED) is one of the most common ophthalmological disorders, resulting from several systemic and ocular etiologies including meibomian gland dysfunction (MGD). During the COVID-19 pandemic, medical students are among the high-risk group for DED, mainly due to the increasing use of a visual display terminal (VDT) for online lectures and psychological stress from encountering several changes. Our study aimed to explore the prevalence of DED using the symptom-based definition and potential risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 39 publications
2
44
1
4
Order By: Relevance
“…Many studies among adults have shown a correlation between DED and contact lens use [10,25]. Several studies among young adults reported similar results [11,22,24,[31][32][33]. DED occurs up to four times more frequently in the population of contact lens users than in the general population [10,25,31].…”
Section: Plos Onementioning
confidence: 86%
See 2 more Smart Citations
“…Many studies among adults have shown a correlation between DED and contact lens use [10,25]. Several studies among young adults reported similar results [11,22,24,[31][32][33]. DED occurs up to four times more frequently in the population of contact lens users than in the general population [10,25,31].…”
Section: Plos Onementioning
confidence: 86%
“…A recent study in Thailand observed a DED prevalence of 70.8% among medical students at Chiang Mai University. This study recognized the impact of VD devices and the psychological stress on DED among students during Covid-19 pandemic [ 11 ]. Similar studies conducted during Covid-19 pandemic reported DED prevalence from 51,8% to 71,7%, using different criteria [ 12 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DED is one of the most common clinically observed conditions worldwide with an estimated population prevalence of 9–30% [ 29 , 30 , 31 ]. Nevertheless, several scientific reports show that the extensive use of computers and monitors, especially since the onset of the SARS-CoV-2 pandemic, has broadened the impact of dry eye-related visual strain by as much as 70.8% in medical students [ 32 ]. In addition to increased screen exposure, the use of face masks has been associated with a 26.09% exacerbation of DED symptoms and there has been an increment of 18.3% in the number of mask-associated dry eyes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, drastic changes in lifestyle and infection control may be associated with DE; however, no study has compared the status of the ocular surface in the general population before and during the pandemic. Some school-based surveys [18][19][20] have reported on the prevalence and severity of DE during this period. However, to the best of our knowledge, clinical data is not sufficient and no study has demonstrated changes in prevalence and objective severity of DE during this period.…”
Section: Introductionmentioning
confidence: 99%